1987
DOI: 10.1128/aem.53.6.1292-1297.1987
|View full text |Cite
|
Sign up to set email alerts
|

Denitrification in Aquifer Soil and Nearshore Marine Sediments Influenced by Groundwater Nitrate

Abstract: We estimated rates of denitrification at various depths in sediments known to be affected by submarine discharge of groundwater, and also in the parent aquifer. Surface denitrification was only measured in the autumn; at 40-cm depth, where groundwater-imported nitrate has been measured, denitrification occurred consistently throughout the year, at rates from 0.14 to 2.8 ng-atom of N g-1 day-'. Denitrification consistently occurred below the zone of sulfate reduction and was sometimes comparable to it in magnit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
2
1

Year Published

1988
1988
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(25 citation statements)
references
References 29 publications
(15 reference statements)
1
21
2
1
Order By: Relevance
“…The rate increases with temperature varied considerably in Lind's three sites. However, the rates at in situ temperatures are all within an order of magnitude and compare well with the reported rates at similar temperatures given by Slater and Capone [ 1987], Bengtsson and Annadotter [1989], and Smith et al [1991], that is, ---10 -1 mg N kg -1 dry sediment per day. As discussed later, the denitdhfication reported by Lind may be autotrophic.…”
Section: C + 4no•-+ 2h20 = 2n 2 + 4hco•-+ Co2supporting
confidence: 87%
“…The rate increases with temperature varied considerably in Lind's three sites. However, the rates at in situ temperatures are all within an order of magnitude and compare well with the reported rates at similar temperatures given by Slater and Capone [ 1987], Bengtsson and Annadotter [1989], and Smith et al [1991], that is, ---10 -1 mg N kg -1 dry sediment per day. As discussed later, the denitdhfication reported by Lind may be autotrophic.…”
Section: C + 4no•-+ 2h20 = 2n 2 + 4hco•-+ Co2supporting
confidence: 87%
“…Shoreline salinity measurements and thermal imagery indicated that though variable along the shore, most discharge of contaminated groundwater occurred through sandy sediments seaward of the Spartina marsh fringe. Thus the direct release of nitrate-contaminated groundwater from high-velocity seeps into Nauset's estuarine waters circumvented the high denitrification potential of low-redox, highly organic marsh and subtidal sediments [Slater and Capone, 1987]. In fact, seepage chamber monitoring suggested little nitrate removal in these sandy surficial sediments.…”
Section: Implications For Nitrogen Loadingmentioning
confidence: 99%
“…Models of the effect of shoreline development on coastal water quality have usually assumed that all nitrogen applied to the land surface as fertilizer and runoff or leached from on-site wastewater disposal systems reaches surface waters; however, recent work on Cape Cod [Valiela et al, 1997] has shown that as little as 20% of nitrogen added to a coastal watershed may reach the downgradient estuary. Denitrification, the microbial conversion of nitrate to dinitrogen gas, can be an important removal process in soils along a groundwater flow path [Slater and Capone, 1987;Smith and Duff, 1988]. Efficiency of nitrogen removal depends on suitable soil conditions, i.e., high organic content and low redox potential, which promote denitrification [Capone and Slater, 1990;Korom, 1992;Starr and Gillham, 1993].…”
Section: Introductionmentioning
confidence: 99%
“…Ling and El-Kadi (1998);Yamaguchi et al (1996);Starr et al (1974);Starr and Gillham (1993);Misra et al (1974);Ardakani et al (1974aArdakani et al ( , 1974b;Lind (1983);Slater and Capone (1987);Anderson (1998);Trudell et al (1986);Smith and Duff (1988);Bengtsson and Annadotter (1989);Francis et al (1989);Obenhuber and Lowrance (1991);Smith et al (1991);Ekpete and Cornfield (1965);Christensen et al (1989);Bradley et al (1992);Tesoriero et al (…”
mentioning
confidence: 99%